CONTESTING AMERICAN ACADEMIC HEGEMONY IN THE AUTHOR GUIDELINES OF SINTA JOURNALS: AN ANALYSIS OF STRUCTURE, LANGUAGE, AND ACADEMIC TOOLS - Basuki, Amin; Adi, Ida Rohani; Munandar, Aris (Rubikon : Journal of Transnational American Studies, 2025)
The dominance of American academic standards has shaped scholarly writing practices worldwide, including in Indonesia. This influence is evident in the adoption of the IMRaD structure, APA citation style, English as the primary language, and reliance on tools such as Turnitin, Grammarly, and reference management software. This article shows how these forms of dominance operate within the author guidelines of Indonesian scholarly journals indexed by SINTA and how local academic actors engage in resistance and negotiation. Drawing on Antonio Gramsci’s theory of hegemony and decolonial perspectives—such as epistemic disobedience (Mignolo), epistemic freedom (Ndlovu-Gatsheni), and ecologies of knowledges (Santos)—the research employs a critical qualitative approach. The data consist of 319 author guidelines from SINTA-accredited journals (levels 1 and 6), analyzed thematically and discursively. The findings show that while many journals conform to American standards, others resist by adopting non-IMRaD structures, alternative citation styles, and Indonesian or Arabic. In addition, local initiatives such as the Garuda portal and institutional repositories provide spaces for resisting epistemic domination. Overall, the article highlights both the persistence of American hegemony and the possibilities for negotiation, contributing to theoretical debates on academic power while offering practical insights for developing more autonomous and context-sensitive academic standards in Indonesia.